STUDI TEKNOMETRIK INDUSTRI KERAJINAN KERAMIK KASONGAN DENGAN MENGGUNAKAN SAGA CERAMIC DAN TOYOTA WAY SEBAGAI BENCHMARKS - , MIFTAH UDIN; , Ir. Alva Edy Tontowi, M.Sc., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to determine level of technology in Kasongan and how to improve it based on Level of technology, Costumer needs and Toyota Way principles. Kasongan was a small and medium enterprises (SME) and one of the prominent ceramic clusters in Yogyakarta province. Primary data were collected through field research and 86 entrepreneurs had been deeply interviewed that consist of 82 small entrepreneurs and 4 grown one. The researches methodology are using technometric (a tool that descripted a technology consist of four aspects: technoware, humanware, infoware, and Orgaware). Also consider today need and competitiveness in future market may follow, using Aritaware (Japanese ceramic) named Saga ceramic cooperative as best class in porcelain and ceramic and Toyota way principles as best practice in manufacture. The study results are combination from Toyota Way and Saga Ceramic Coperative as recommendation of Kasongan improvement : a). Technoware: implementation of Jidoka and 5-S Principle in production process, mechanical means may follow, Implementation of cooperation projects with ISI Yogyakarta and PPPPTK in product development, Set of price by cost reduction to maximize profit. b). Humanware: Increasing costumer service using respect to costumer principle and labor empowerment through training with Kasongan artist. c). Infoware: Implementation of updating all management information in monthly as public relation. d) Orgaware: Cooperative empowerment.